Comparing Aggradation, Superelevation, and Avulsion Frequency of Submarine and Fluvial Channels - Jobe, Zane R.; Howes, Nick C.; Straub, Kyle M.; Cai, Dingxin; Deng, Hang; Laugier, Fabien J.; Pettinga, Luke A.; Shumaker, Lauren E. (Frontiers in Earth Science, 2020)
Constraining the avulsion dynamics of rivers and submarine channels is essential for predicting the distribution of sediment, organic matter, and pollutants in alluvial, deltaic, and submarine settings. We create a geometric channel-belt framework relating channel, levee, and floodplain stratigraphy that allows comparative analysis of avulsion dynamics for rivers and submarine channels. We utilize 52 channel-overbank cross sections within this framework to provide avulsion criteria for submarine channels, and how they differ from rivers. Superelevation and a new channel-floodplain coupling metric are two key parameters that control channel-belt thickness in both rivers and submarine channels. While rivers only superelevate 1 channel depth above the floodplain prior to avulsion, submarine channels are more stable during aggradation, with superelevation values commonly >3 channel depths. Additionally, channel-floodplain coupling in rivers is often weak, with floodplain aggradation negligible compared to channel aggradation, making rivers avulsion-prone. However, floodplain aggradation is more significant for submarine channels, resulting in stronger channel-floodplain coupling and thus a decreased potential for avulsion. The combination of enhanced superelevation and strong channel-floodplain coupling results in submarine channel-belts that can be as thick as ~ 10 channel depths, while fluvial channel belts are limited to 2 channel depths. Submarine channels are more stable because turbidity currents have ~50x lower density contrast between flow and ambient fluid as compared to rivers. This density contrast creates far less potential energy for avulsion, despite the much greater relief of submarine levees compared to fluvial levees. The modern Amazon submarine channel showcases this stability, with a channel belt that is ~ 5 channel-depths thick for more than 400 streamwise km, which is more than twice the superelevation that a river is capable of. We interpret that enhanced floodplain aggradation and levee aggradation (and thus superelevation) in submarine channel belts are promoted by unique submarine flow characteristics, including turbidity current overspill, flow-stripping, and hemipelagic processes. We emphasize that rivers and submarine channels display very different avulsion dynamics and frequencies, profoundly affecting the stratigraphic architecture of channel-belt and downstream distributary deposits.